Responsabilidad penal del administrador de la sociedad matriz por los delitos cometidos en el ámbito de las filiales - Blanco Cordero, Isidoro (2025)
This study analyzes the grounds for attributing criminal liability to the administrator of a parent company for offenses committed by subsidiaries within corporate group structures. It explores the challenges posed by the coexistence of joint business management and the legal independence of each company, especially when decisions made at the parent level influence unlawful conduct in the subsidiaries. The study highlights the need to establish clear criteria for assigning criminal liability to the administrator of the parent company, ensuring that liability is only imposed when their action or omission has been decisive in the commission of the offense, thus preventing both impunity and a disproportionate extension of liability.